Urban waste fertilizer: effects on yield, nutrient dynamics, and potentially toxic element accumulation - Marie Reimer; Kurt Möller; Jakob Magid; Sander Bruun (Nutrient Cycling in Agroecosystems, 2025)
Recycling nutrients contained in urban wastes to agriculture is essential in a circular economy. This study simultaneously compares different recycled fertilizers (household waste compost, sewage sludge, human urine) with mineral fertilization and animal manures. Tested were their long-term effects on yield, nutrient budgets, potentially toxic element (PTE) accumulation, and nitrogen (N)/carbon (C) cycle (among others N efficiency, N losses, soil C). Therefore, data from a long-term field trial and predictions from the soil–plant-atmosphere model Daisy were evaluated. Based on trial data, human urine performed similar to the mineral fertilization for yield, N efficiency (mineral fertilizer equivalent (MFE) = 81%), and nutrient budget, while sewage sludge and compost were comparable to animal manures in terms of having lower yields, N efficiencies (MFE 70% and 19% respectively) and higher nutrient imbalances, especially P and S surpluses. Compost and sewage sludge applications resulted in net PTE inputs. Yet, plant uptake and soil accumulation seemed neglectable. Model outputs predicted N losses of 34–55% of supplied N. Losses were highest for compost, followed by deep litter, manure, sewage sludge, human urine, mineral fertilization, and slurry. Nitrate leaching was the main loss pathway (14–41% of N input). Within the compost and straw-rich manure fertilization, about 25% of applied N was stored in the soil which was accompanied by an increase in soil C. The study suggests substitution of established fertilizers with recycled ones is feasible. Thereby each fertilizer has advantages and disadvantages and thus should be utilized according to its strength or in mixtures.